Medical Communication during the Transition to Palliative Care in Pediatric Oncology in Hungary-The Parents' Perspective - Enikő Földesi; Szilvia Zörgő; Judit Nyirő; György Péter; Gábor Ottóffy; Peter Hauser; Katalin Hegedűs (MDPI AG, 2022)
The transition to palliative care (PC) is a critical aspect of pediatric oncology, and it requires a high level of communication skills from doctors, which could be best judged by the parents of children who have died from cancer. Our aim was to explore the parents' perspectives regarding the timing of the consultation on the implementation of PC, as well as facets of verbal and nonverbal communication in Hungary. Semistructured interviews were conducted with parents who had lost a child to cancer within the past 1-5 years. Interview transcripts (n = 23) were scrutinized with interpretative phenomenological analysis. The parents frequently associated palliation with end-of-life care and they clearly delimited the transition to PC after curative treatments had been exhausted. The parents were ambivalent with regard to the use of the word "death" during this consultation, and they often did not receive information on what to expect (e.g., regarding symptoms) or on who to turn to for further information or support (e.g., concerning bereavement). Although significant progress could be observed in the organization of pediatric palliative care in Hungary, there is still no widely accepted communication method for the transition to sole PC. There is a need for a culturally sensitive approach to refining the recommendations on the word use and communication protocol in pediatric PC in Hungary.